Capillary basal lamina in human brain and spinal cord has fibrillar collagen type I and type III: Ignorance may not be bliss - Lin, Wen-Lang; Dickson, Dennis W. (Free Neuropathology, 2025)
The capillary basal lamina (BL) located between the endothelial cell, pericyte and perivascular astrocyte plays important roles in normal and diseased central nervous system (CNS). Using immunohistochemistry (IHC), electron microscopy (EM) and post-embedding immunogold EM (IEM), we studied capillary basal lamina (BL) in biopsy and autopsy tissues of human CNS from cases with and without significant brain pathology and aged from 4 days to 49 years. In all cases, IHC showed, in the BL of microvessels, immunoreactivity for collagen types I, III, IV, VI and fibronectin. EM revealed fusion of the BL of capillary endothelial cells or pericyte with perivascular astrocyte BL, which was focally split, resulting in expanded spaces bordered by BL and containing striated fibrils. There was no significant thickening of fused or split BL. IEM showed localization of collagen I and III to banded fibrils, and of collagen IV to split and fused BL. These characteristic ultrastructural findings in human capillary BL were not found in normal or transgenic mice. Our observations of fibrillar collagen in young individuals complement previous observations of similar findings in older individuals. This raises the possibility that fibrillar collagen in human vascular BL plays a significant role in CNS capillary physiology and pathophysiology. The species-specific differences in capillary morphology between humans and mice might have relevance to poor correlations between benefits of immunotherapy and drug treatment in mice compared with human.